Endoscopic Self-Expandable Metallic Stent Insertion without Fluoroscopic Guidance Is Feasible and Safe for Acute Colonic Obstruction Caused by Colorectal Cancer. (10th January 2020) - Feng, Yadong; Yu, Qian; Li, Ming; Xu, Wei; Zhu, Ye; Liu, Yang; Shi, Ruihua
Abstract : Aims . Endoscopic self-expandable metallic stent (SEMS) insertion for acute colonic obstruction caused by colorectal cancer (CRC) is always performed under fluoroscopic guidance. This study evaluated the feasibility and safety of an endoscopic stenting procedure without fluoroscopic guidance. Methods . A total of 36 patients with an acute colonic obstruction caused by CRC underwent endoscopic SEMS insertion using a colonoscope without fluoroscopic guidance, followed by analyses of the technical and clinical success and short-term complications. Results . Total technical success rate and clinical success rate were 91.7% and 86.1%, respectively. The mean procedure time was 21.2 ± 10.3 minutes. There was no stent dislodgement. One case of hematochezia and two cases of tenesmus occurred in patients with left-sided complete obstructions. No other short-term complications occurred. Procedure time, technical success, and clinical success rate were 16.3 ± 9.4 minutes, 93.1%, and 89.6% for left-sided obstructions, respectively, and were 26.8 ± 10.7 minutes, 85.7%, and 71.4% for right-sided obstructions, respectively. For complete obstructions, procedure time, technical success, and clinical success rate were 22.5 ± 8.9 minutes, 90%, and 83.3%, respectively. In the incomplete cases, procedure time, technical success, and clinical success were 13.5 ± 6.7 minutes, 100%, and 100%, respectively. Technical success, clinical success, and short-term complications were not differed between lesion locations and degrees. Conclusions . This simple technique is feasible and safe for palliation of acute colonic obstruction caused by CRC.